ANALYSIS OF SUCCESSFUL RESUSSITATION IN PRE–HOSPITAL STAGE IN UKRAINE - Krylyuk, V.O.; Tsymbalyuk, H.Y. (World of Medicine and Biology, 2020)
The article presents a retrospective analysis of 384 cases of successful cardiopulmonary resuscitation at the prehospital stage in Ukraine. The study was conducted in the period from 2017 to 2019. The patients' general group was divided into two subgroups depending on the initial rhythm of sudden circulatory arrest: defibrillation and non–defibrillation rhythms. In each of the subgroups studied: age of patients, causes of sudden cessation of blood circulation, location, home care, time of resuscitation, methods of restoring airway patency, the presence of self–breathing in the post–resuscitation period, and level of consciousness. The subgroup with non–defibrillation rhythms included 199 cases (51.8%), the subgroup with defibrillation rhythms – 185 cases (48.2%). It was determined that the main cause of circulatory arrest in both subgroups was an acute coronary syndrome.
Keywords: sudden cardiac arrest; cardiopulmonary resuscitation; pre–hospital stage; emergency medicine care